농업 경영체의 조직화 효과와 활성화 방안 - 황의식 (한국농촌경제연구원, 2008)
The objective of this study is to figure out the effect of systematization among agricultural enterprises, surveying the cases of systematized farming at the village level. Then, we derive a scheme to revitalize village farming through systematization. To foster full-time specialized formers has been the me of core measures by governmert to strenghten the compefitiveness of agriculture. Even so, prime full-time farmers cannot cover all the land to be cultivated, and thus we also need to develop measures that can enhance the efficiency of farming by all types of agricultural enterprises including small poor farms. The systematization of village farming enables corporate management at the village level through economies of scale based on a management strategy incorporating all the relevant production resources such as land, labor, and capital on a long-term basis. We can also expect to see new ways of land usage, adoption of new production technologies, and business-minded decision making from the systematization. For our case study, we surveyed the following agricultural enterprises: Natur, an agricultural corporation; a farm under direct management of the Sunchon agricultural cooperative; Jusansarang, an agricultural cooperative firm as well as the farmers who rent out the cultivated land to them. Researchers: Eui-Sik Hwang, Hogun Chong E-mail address: eshwang@krei.re.kr